PENDEKATAN ILMU KOMUNIKASI MODERN Sebuah Metodologi Tafsir Al-Qur’an Kontemporer - M Akib (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2019)
the science is real communication has a strong scientific foundation, as derived from the Qur'an. Through Qur'an bersosial people are invited to live and communicate. In this case the Qur'an gives positive values yag should be developed and when talking about the concept of science communication in the Qur'an implies how the Qur'an describes the concepts of Islamic communication based content in it , This thesis also explains that the decline in the Qur'an as the word of God to men is according to man's knowledge of the communication. It follows that the Qur'an is indeed very appropriate and certainly fits the human ability. From these results it can be concluded with a dia-gram that explains the mutual communication between modern scien-ce with the explanation of the Qur'an.